Impact of stent size on angiographic and clinical outcomes after implantation of everolimus-eluting bioresorbable scaffolds in daily practice: Insights from the ISAR-ABSORB registry - Wiebe, Jens; Hoppmann, Petra; Kufner, Sebastian; Harada, Yukinori; Colleran, Roisin; Michel, Jonathan; Giacoppo, Daniele; Schneider, Simon; Cassese, Salvatore; Ibrahim, Tareq; Schunkert, Heribert; Laugwitz, Karl-Ludwig; et al. (EuroIntervention, 2016)
Aims: We sought to evaluate the impact of stent size on angiographic and clinical outcomes after implantation of everolimus-eluting bioresorbable stents (BRS) in routine clinical practice. Methods and results: All consecutive patients undergoing BRS implantation at two centres in Munich, Germany, were included prospectively. The patient population was divided according to the diameter of the implanted BRS. Angiographic surveillance was scheduled at six to eight months after stent implantation and films were analysed in a core laboratory. A BRS with 2.5 mm diameter was implanted in 101 patients and BRS >2.5 mm diameter in 318. Baseline patient characteristics were similar in both groups. Reference vessel diameter was 2.36±0.22 mm in patients with an implanted 2.5 mm BRS and 3.03±0.40 mm in the other group (p<0.001). At angiographic follow-up, in-stent late luminal loss (0.28±0.47 mm vs. 0.25±0.52 mm, p=0.74) was similar in both groups, though binary angiographic restenosis was numerically higher in patients treated with a 2.5 mm BRS (12.5% vs. 6.1%, p=0.05). After 12 months, the rate of the composite of death, myocardial infarction or target lesion revascularisation was 15.7% vs. 12.3% (p=0.49). Definite stent thrombosis was detected in 1.0% vs. 3.1% (p=0.31). Conclusions: In patients treated with BRS in routine clinical practice, angiographic and clinical outcomes were comparable in patients treated with a 2.5 mm stent as compared with those treated with a larger stent size.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Angiographic surveillance; Bioresorbable scaffold; Bioresorbable stent; Restenosis; Stent thrombosis; Vessel size